PKMYT1 as a Potential Target to Improve the Radiosensitivity of Lung Adenocarcinoma - Long, Huan-ping; Liu, Jia-qing; Yu, Yang-yang; Qiao, Qiao; Li, Guang (Frontiers in Genetics, 2020)
Objective: This article is dedicated to finding important genes related to the prognosis of lung adenocarcinoma(LUAD), and looking for a new gene that may affect tumor radiosensitivity and conducting basic experiments to verify the relationship between this gene and radiosensitivity of LUAD. Methods: The gene expression profiles GSE32863, GSE33532 and GSE43458 were obtained from NCBI-GEO. GEO2R and venn diagram were used to identify up-regulated genes. STRING and Cytoscape were applied to develop a proteinprotein interaction network (PPI) and analyze the modules. The Database for Annotation, Visualization and Integrated Discovery (DAVID) was used to process GO and KEGG pathway analysis. The Kaplan Meier plotter and Gene Expression Profiling Interactive Analysis (GEPIA) were applied to get the significant prognostic information and differential expression between LUAD tissues and normal lung tissues. Western blotting and Q-PCR were used to detect the expression of PKMYT1 in tissues. Small interfering RNAs (siRNAs) were used to knockdown PKMYT1. Colony survival experiment was used to assess the effect of PMYT1 on the radiosensitivity of tumor cells. Cell-cycle analysis was used to assess cell cycle distribution.Results: We identified 14 genes (PKMYT1, TTK, CHEK1, CDC20, PTTG1, MCM2, CDC25C, MCM4, CCNB1, CDC45, MAD2L1, CCNB2, BUB1, CCNA2) that are important for LUAD and may be potential therapeutic targets. We confirmed that PKMYT1 is highly expressed in LUAD and firstly demonstrated that artificially silencing the expression of PKMYT1 can abrogates IR-induced G2/M phase arrest and increase the sensitivity of cancer cells to radiation. Conclusion: In summary, we obtained 14 core genes related to the poor prognosis of LUAD via bioinformatical analysis. We identified that PKMYT1 was significantly up-regulated in LUAD tissues and firstly demonstrated that knockdown of PKMYT1 can eliminate the radiation-induced G2 / M arrest, resulting lower survival rate when cells receiving radiation therapy.Our findings suggested that PKMYT1 is a promising target to improve the radiosensitivity of LUAD.